Voluntary, temporary out-of-home firearm storage: a survey of law enforcement agencies in two states - Marian E. Betz; Sara Brandspigel; Leslie M. Barnard; Rachel L. Johnson; Christopher E. Knoepke; Ryan A. Peterson; Frederick P. Rivara; Ali Rowhani-Rahbar (BMC, 2022)
Abstract Background Temporary, voluntary storage of firearms away from the home during times of risk is a recommended strategy for suicide prevention. Law enforcement agencies (LEAs) are often suggested as storage sites, and online maps in Colorado and Washington display LEAs willing to consider storage. Questions remain about the experiences and views of LEAs, including barriers to providing storage. Methods  LEAs in Colorado and Washington were invited to complete a survey via mail or online from June to July 2021; invitations were sent by email and mail, with telephone calls to non-responders. Survey data were analyzed using descriptive statistics, with testing between states and other subgroups using Fisher's exact tests. Results Overall, 168 LEAs in Colorado (n = 91) or Washington (n = 77) participated (40% participation rate). Of those, 53% provided temporary, voluntary storage upon request by community members at the time of the survey. More LEAs said they had ever provided storage when the requester was under a court order (74% overall). Over half (60%) of responding LEAs had received at least one storage request in the prior 12 months. Many (41%) said they had declined to return a firearm after temporary storage due to safety concerns. Most LEAs supported engagement in suicide prevention (89%) and provision of community services (77%), but they simultaneously preferred being a storage option of last resort (73%). Factors negatively influencing storage provision included liability and funding concerns. Conclusions In Colorado and Washington, half of LEAs currently offer temporary, voluntary firearm storage upon request. While LEAs support suicide prevention and community engagement, broader provision of storage and participation in online maps may be limited by logistic, liability, and financial concerns. Addressing these barriers may facilitate broader suicide prevention efforts.